Odpowiedź:
[tex]f'(3)=18[/tex]
Szczegółowe wyjaśnienie:
Definicja pochodnej:
[tex]$f'(x_{0})= \lim_{h \to 0} \frac{f(x_{0}+h)-f(x_{0})}{h} [/tex]
Funkcja:
[tex]f(x)=2x^{2}+6x-5[/tex]
[tex]x_{0}=3[/tex]
Mamy:
[tex]$f'(x_{0})= \lim_{h \to 0}\frac{2(x_{0}+h)^{2}+6(x_{0}+h)-5-2x_{0}^{2}-6x_{0}+5}{h}= [/tex]
[tex]$= \lim_{h \to 0} \frac{2x_{0}^{2}+4x_{0}h+2h^{2}+6x_{0}+6h-5-2x_{0}^{2}-6x_{0}+5}{h}= [/tex]
[tex]$= \lim_{h \to 0} \frac{4x_{0}h+2h^{2}+6h}{h}= \lim_{h \to 0} 4x_{0}+2h+6=4x_{0}+6[/tex]
Teraz wystarczy podstawić [tex]x_{0}=3[/tex], aby otrzymać:
[tex]f'(3)=4 \cdot 3+6=18[/tex]